Treatment of Pesticide Wastewater by Physicochemical and Fenton Processes - OZDEMIR, CELALETTIN; SAHINKAYA, SERKAN; ONUCYILDIZ, MUSTAFA (Asian Journal of Chemistry, 2010)
The process of pesticide removal from industrial wastewater using which chemical, vacuum-chemical and Fenton's reactions have been analyzed. Fenton process is attractive alternative to conventional oxidation processes in effluent treatment of recalcitrant compounds. The aim of this study is to evaluate the efficiency of chemical, vacuum and Fenton processes for the reduction of chemical oxygen demand in wastewaters from pesticide industry. In this study wastewater from pesticide industry was used. Whereas in the chemical procedure [Ca(OH)2 and KMnO4], the chemical oxygen demand removal efficiency is 94.9 %; in the vacuum-Ca(OH)2 + KMnO4 system (with 250 mg/L KMnO4, 1 mL H2SO4, 5 mg/L polyelectrolyte and 2000 mg/L CaOH application) this efficiency was 97.8 %; and a 99.8 % KOI removal efficiency was obtained by the Fenton process (the optimum ratio of [Fe2+] to [H2O2] was 1:1.56 (mM/mM), at pH 3.0).